PERBANDINGAN HASIL BELAJAR MAHASISWA SELEKSI TERTULIS DENGAN NON TERTULIS PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 176-183 . Rido Aditya Roja (CIVED, 2013)
This research is using quantitative method in the type of descriptive-comparative that purposed to find out the comparison of student grades/IP (learning result) in first and second semester for student of written and non-written selection at construction engineering education program civil engineering FT-UNP. Population in this research is students of construction engineering education program civil engineering FT-UNP year of entranced 2010-2011, which are amounted to 176 students. Sampling collection technique is determined with proportional stratified random samping. Data collection technique is documentation. Results from this research thitung = 2.10 > ttabel= 1.980, which is mean that there is a significant comparison student of written and non-written selection at construction engineering education program civil engineering FT-UNP, for semester two research thitung = 0,95 < ttabel= 1.980, which is mean that there is not significant comparison student of written and non-written selection at construction engineering education program civil engineering FT-UNP, while for one year of study thitung = 1.616 < ttabel 1.980, which is mean that there is not significant comparison student of written and non-written selection at construction engineering education program civil engineering FT-UNP. Key words : written selection, non-written selection.